Heterosis unveiled in root-related traits and saikosaponins content between triploid F1 hybrids and parental Bupleurum chinense DC. - Mo, Chuanxin; Chen, Wenshuai; Lv, Zhuolin; Zhao, Jun; Li, Yuchan; Shi, Qiannan; Dong, Kaimi; Wei, Zhen; Yu, Zeru; Wang, Xueling; Xin, Chao; Ni, Zhen; et al. (Frontiers in Plant Science, 2026)
The root biomass and saikosaponins yield of Bupleurum chinense DC. are crucial factors determining its economic value. This study developed triploid F1 hybrid materials of the B. chinense by crossing a diploid (2n=2x1 = 12, x1 = 6) maternal parent with a tetraploid (2n=4x2 = 20, x2 = 5) paternal parent. The resulting hybrids exhibited a stable intergenomic karyotype (2n=x1+2x2 = 16) and significant heterosis. Two-year field trials confirmed strong over-dominance in root architecture, with root dry weight exceeding that of the diploid and tetraploid parents by 37.3% and 166.5%, respectively. The yield of the bioactive compounds saikosaponin A (13.42 mg) and D (13.20 mg) increased by an average of 60.7% and 57.5%, respectively, compared to the diploid parent, highlighting substantial potential for pharmaceutical development. Based on the transcriptome comparison in the seedling and maturity stage of the root, the remarkable heterosis might be supported by unique genomic architecture and sophisticated transcriptional reprogramming. The intergenomic imbalance, likely provide a stable foundation for heterosis by facilitating functional compartmentalization and synergistic interaction between the parental subgenomes. Transcriptome analysis revealed that the heterotic traits were arranged by a complex relationship of gene networks: root morphology was optimized through the additive and transgressive expression of hormone signaling genes, while the enhanced synthesis of saikosaponins was driven by the synergistic expression of key biosynthetic genes. This research provides a novel strategy for exceed conventional plant breeding by demonstrating engineered genomic asymmetry, specifically intergenomic triploid and could help to unlock superior and stable heterosis.